Communicate with courage : taking risks to overcome the four hidden challenges - Gladieux, Michelle D. (Berrett-Koehler Publishers, Inc., 2023)
"Clear communication requires the courage to confront the psychological blocks that are holding you back. Learn how to become a fearless and peerless communicator. As a lifelong communication coach, Michelle Gladieux has discovered the four sneaky psychological obstacles that can keep you from becoming an effective communicator: Hiding-Fearing your low self-confidence will expose your supposed weaknesses; Defining-Putting too much stock into your assumptions and being quick to judge right and wrong; Rationalizing-Using "being realistic" to shield yourself from taking chances, engaging in conflict, or doing other scary but potentially rewarding actions; Settling-Stopping at "good enough" instead of pushing for something better. What all these challenges have in common is they require taking risks-to reveal yourself, to question your beliefs, to take a leap of faith, or to move out of your comfort zone. As a response, each chapter includes a Pro Move, or a best practice, and an exercise designed to help you overcome your fears and become a powerful communicator. Courageous communication requires self-knowledge, practice, and a fierce desire to continually improve; this book is like having an expert coach along with you for every step of the journey"--